2018
DOI: 10.1111/iej.12919
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of various irrigation protocols on organic tissue removal from simulated internal resorption defects

Abstract: The use of a NaOCl + HEBP mixture activated with XP-endo Finisher was an effective irrigation regimen for removing simulated organic tissues from artificial internal root resorption cavities in the straight root canals of single-rooted teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 16 publications
2
42
0
5
Order By: Relevance
“…The canal is wide due to incomplete root development (A); A gutta percha is placed which reached up to the area of resorption (B); Repair of the apical part by mineral trioxide aggregate (C); The remaining canal was sealed by gutta-percha and sealer (D); One month follow-up (E); After one year (F) used for 5 min followed by 2% chlorhexidine for 30 sec as suggested by some of the previous studies. [23][24] Calcium hydroxide also used as an intracanal medicament and a favorable result was achieved in the present and previous studies. [25][26] Repair with mineral trioxide aggregate Dr. Hossain: In the case when resorptive defect was seen on the apical part of the root canal with perforation of the root, this can be repaired by mineral trioxide aggregate because it is biocompatible, has superior sealing ability, induces osteogenesis and cementogenesis as well as well tolerated in the periapical tissue.…”
supporting
confidence: 77%
“…The canal is wide due to incomplete root development (A); A gutta percha is placed which reached up to the area of resorption (B); Repair of the apical part by mineral trioxide aggregate (C); The remaining canal was sealed by gutta-percha and sealer (D); One month follow-up (E); After one year (F) used for 5 min followed by 2% chlorhexidine for 30 sec as suggested by some of the previous studies. [23][24] Calcium hydroxide also used as an intracanal medicament and a favorable result was achieved in the present and previous studies. [25][26] Repair with mineral trioxide aggregate Dr. Hossain: In the case when resorptive defect was seen on the apical part of the root canal with perforation of the root, this can be repaired by mineral trioxide aggregate because it is biocompatible, has superior sealing ability, induces osteogenesis and cementogenesis as well as well tolerated in the periapical tissue.…”
supporting
confidence: 77%
“…According to six of the included studies, the XP-Endo Finisher instrument (XPF) showed a greater root canal cleaning efficacy than the passive ultrasonic irrigation technique (PUI) [5,[15][16][17][18][19]. On the contrary, seven articles stated that the passive ultrasonic irrigation technique and XP-Endo Finisher showed no significant differences among them in removing root filling material from canal root, and that both protocols have a greater efficacy than conventional needle irrigation procedure (CNI) [10,12,[20][21][22][23][24].…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…, , Ulusoy et al . ). Bovine meat was used as an organic tissue sample rather than pulp because it is widely available, has a uniform composition that resembles pulp tissue and can be cut into sections of very similar size and weight, allowing for sample standardization (Stojicic et al .…”
Section: Discussionmentioning
confidence: 97%